(untitled) (International Journal of Engineering and Computer Science, 2017)
As in real world, in virtual world also there are people who want to take advantage of you by exploiting you whether it would be your money, your status or your personal information etc. MALWARE helps these people accomplishing their goals. The security of modern computer systems depends on the ability by the users to keep software, OS and antivirus products up-to-date. To protect legitimate users from these threats, I made a tool (ADVANCE DYNAMIC MALWARE ANAYSIS USING API HOOKING) that will inform you about every task that software (malware) is doing over your machine at run-time